„The End" i projekt happy endu. O funkcji piosenki w "Czasie Apokalipsy" F.F. Coppoli - Igielska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
„The End” and a Project of Happy End. On the Function of Song in F.F. Coppola’s „Apocalypse Now” In his brilliant analysis and interpretation of the famous song The End of The Doors Werner Faulstich showed that this piece is built on the formal structure of Greek tragedy. This article is an attempt at developing his idea by putting it in context of Francis Ford Coppola’s film, Apocalypse Now: beginning with the description of the structure and dramaturgy of film exposition, then showing the place of the song in the film narration and composition, at last stressing its connection with the plot – not only with the prologue and the end of Coppola’s work, but also with mythological subject and message of his film